2011
DOI: 10.1097/ccm.0b013e3181feb46a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein levels are markers of pulmonary vascular permeability and degree of lung injury in critically ill patients with or at risk for acute lung injury/acute respiratory distress syndrome*

Abstract: In critically ill patients, decreased plasma albumin and transferrin levels parallel increased pulmonary vascular permeability irrespective of underlying disease and fluid status. While normal levels help to exclude acute respiratory distress syndrome, hypoalbuminemia and hypotransferrinemia increase the diagnostic accuracy of the American European Consensus Conference criteria and lung injury score for elevated pulmonary vascular permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 35 publications
1
41
1
Order By: Relevance
“…Regardless of this threshold, our results suggest that LV diastolic function contributes to the development of PGD. While previous work suggested that plasma albumin is inversely related to pulmonary vascular permeability in patients at risk for acute lung injury (57,58), the association between diastolic function and PGD was not affected by albumin level in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…Regardless of this threshold, our results suggest that LV diastolic function contributes to the development of PGD. While previous work suggested that plasma albumin is inversely related to pulmonary vascular permeability in patients at risk for acute lung injury (57,58), the association between diastolic function and PGD was not affected by albumin level in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…Large number of the studies on this issue have focused on ICU adult patients generally and specific groups of patients with a variety of pathologic conditions. 8 However, there is a paucity of data on the incidence and significance of hypoalbuminemia in critically ill children admitted to intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides hypervolemia and heart failure, high level of inflammation in ESRD patients contributes to lung congestion due to microvascular lung disease, provoking capillary leakage. 2,3 Lung congestion is a strong prognostic marker of cardiac events and death among ESRD patients submitted to HD. HD patients with severe congestion have a 4.2-fold higher risk of death and a 3.2-fold higher risk of cardiac events, like myocardial infarction, angina, heart failure and arrhythmia.…”
Section: Introductionmentioning
confidence: 99%